Regulating billions of blood platelets: glycans and beyond - Grozovsky, Renata (Blood, 2015)
The human body produces and removes 10(11) platelets daily to maintain a normal steady state platelet count. Platelet production must be regulated to avoid spontaneous bleeding or arterial occlusion and organ damage. Multifaceted and complex mechanisms control platelet production and removal in physiological and pathological conditions. This review will focus on different mechanisms of platelet senescence and clearance with specific emphasis on the role of posttranslational modifications. It will also briefly address platelet transfusion and the role of glycans in the clearance of stored platelets.